Consideration of solar activity by determining parameters of the generation system based on RES; GREEN - 2022. Студенческие исследования в области экологии, инженерии и природы; Ч. 1 - Malkova Ya. Yu. Yana Yurievna (2022, 2022)
Заглавие с экрана